2002
DOI: 10.4219/jsge-2002-374
|View full text |Cite
|
Sign up to set email alerts
|

The Moral Reasoning and Scientific Argumentation of Gifted Adolescents

Abstract: The purpose of this study was to explore the moral reasoning and scientific argumentation of Finnish adolescents who are gifted in science. The pupils (N = 31) participated in the gifted program at the University of Helsinki. The general intellectual ability of these students was measured by the Raven test (SMP), and their moral reasoning was measured by the Defining Issues Test (DIT). In qualitative essays and interviews, the pupils were asked to identify moral dilemmas in science and provide solutions to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
33
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 10 publications
9
33
0
3
Order By: Relevance
“…Results showed that Science topics within a social context generate moral dilemmas. Tirri and Pehkonen (2002) support what Sadler and Zeidler (2003) suggest. They observed that students with the highest scientific skills were not always the ones with the highest moral reasoning skills.…”
Section: Related Researchsupporting
confidence: 80%
See 2 more Smart Citations
“…Results showed that Science topics within a social context generate moral dilemmas. Tirri and Pehkonen (2002) support what Sadler and Zeidler (2003) suggest. They observed that students with the highest scientific skills were not always the ones with the highest moral reasoning skills.…”
Section: Related Researchsupporting
confidence: 80%
“…Some authors have observed that when Science lessons are learned without reference to social context they do not generate moral dilemmas (Clarkeburn et al 2002;Settelmaier 2003;Tirri and Pehkonen 2002;Walker et al 2000). These authors report that in order to promote moral development in students, Science classes should include discussions related to ethical aspects of Science relevant to the students.…”
Section: Related Researchmentioning
confidence: 96%
See 1 more Smart Citation
“…Ahlaki ikilemlerden karakter eğitiminin toplumsal sorunlarla ilişikilendirilerek verilmesinde yararlanılabilir. Tirri ve Pehkonen (2002) fen alanındaki üstün yetenekli ergenlerin ahlaki sorgulama ve bilimsel tartışmalarını incelemiştir. Çalışmanın sonuçları öğrencilerin tartışmadaki ahlaki ikilemle ilgili farklı boyutları betimlediklerini göstermiştir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…Hernstein and Murray (14), for example, claim that people with lower IQ are more prone to deviant and criminal behaviour, while those with IQ above 125 (so called »cognitive elite«) commit crimes to a much lesser extent, engage less in excessive consumption of drugs and alcohol, have lower unemployment rate, and are usually successful in their careers. In addition, a whole series of studies has reported that gifted individuals have better developed moral reasoning than their peers (15)(16)(17).…”
Section: Measuring Moral Developmentmentioning
confidence: 99%